2018
DOI: 10.1055/a-0804-2715
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Addison’s Disease

Abstract: Addison’s disease – the traditional term for primary adrenal insufficiency (PAI) – is defined as the clinical manifestation of chronic glucocorticoid- and/or mineralocorticoid deficiency due to failure of the adrenal cortex which may result in an adrenal crisis with potentially life-threatening consequences. Even though efficient and safe pharmaceutical preparations for the substitution of endogenous gluco- and mineralocorticoids are established in therapy, the mortality in patients with PAI is still increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 79 publications
(95 reference statements)
1
56
0
13
Order By: Relevance
“…A steady increase of the prevalence of AD has been observed over the years, particularly in women [216]. AD clinically occurs with adrenal insufficiency, caused by an autoimmune-mediated destruction of adrenal cortex [217]. Although the pathogenesis of AD has not been completely elucidated, an interplay role between HLA haplotypes and environmental factors has been postulated [218,219].…”
Section: Addison's Diseasementioning
confidence: 99%
“…A steady increase of the prevalence of AD has been observed over the years, particularly in women [216]. AD clinically occurs with adrenal insufficiency, caused by an autoimmune-mediated destruction of adrenal cortex [217]. Although the pathogenesis of AD has not been completely elucidated, an interplay role between HLA haplotypes and environmental factors has been postulated [218,219].…”
Section: Addison's Diseasementioning
confidence: 99%
“…4B), thereby revealing the mechanism through which Dex but not CpdX compounds induces skin atrophy, osteoporosis, and inhibition of corticoids synthesis. Long-term treatments with a high dose of synthetic GCs (e.g., Dex and prednisolone) are known to induce an adrenal gland atrophy, similar to that occurring in Addison's disease (38). We have shown that a long-term treatment with Dex induces an adrenal insufficiency, whereas a similar treatment with CpdX, CpdX-D3, or any of their enantiomers did not induce an atrophy of the adrenal fasciculata and glomerulosa zones where the corticosterone and the aldosterone are produced, respectively.…”
Section: Several Of the Debilitating Side Effects Generated By Adminimentioning
confidence: 99%
“…This special issue also highlights the importance of non-tumorous adrenal diseases with high morbidity, such as Addison's disease and congenital adrenal hyperplasia. In a timely review, Barthel et al [19] reflect upon current treatment standards in Addison's disease and improvements in long-term care. Reisch [20] summarizes the long-term sequelae observed in patients with congenital adrenal hyperplasia.…”
Section: The Adrenal Cortex Conference In Munich 2018mentioning
confidence: 99%